Validating a Tourism Instrument in Rural Tourism Destination. A Test on Bario - Abang Azlan, Mohamad; May Chiun, Lo; Peter, Songan; Alvin Wee, Yeo; Vikneswaran, Nair (Societe de Physique et d'Histoire Naturelle de Geneve, 2012)
Past researches have observed a shift in the dimensions of tourism scales. The purpose of the research reported here was to test empirically and to validate the conceptualization of tourism scales that consists of six dimensions based on Ap and Crompton’s (1998) research. Data was gathered through a survey using a structured questionnaire to local communities at Bario Highland, a rural tourism destination at Sarawak with a total of 66 respondents. Findings obtained from the confirmatory factor analysis and reliability tests indicated that only five dimensions of social cultural, amenities, entertainment, values and community attitudes are highly suited for measuring the tourism scales at rural tourism destination, also proving that the instrument is applicable in the Malaysian rural tourism industry. Through the correlation analysis, it was shown that these dimensions are confirmed of their distinct dimensions from one another. Implications regarding the value of conducting validity and reliability test for practitioners and researchers are discussed.